2013
DOI: 10.1038/nature12323
|View full text |Cite
|
Sign up to set email alerts
|

Recalibrating Equus evolution using the genome sequence of an early Middle Pleistocene horse

Abstract: The rich fossil record of equids has made them a model for evolutionary processes. Here we present a 1.12-times coverage draft genome from a horse bone recovered from permafrost dated to approximately 560-780 thousand years before present (kyr BP). Our data represent the oldest full genome sequence determined so far by almost an order of magnitude. For comparison, we sequenced the genome of a Late Pleistocene horse (43 kyr BP), and modern genomes of five domestic horse breeds (Equus ferus caballus), a Przewals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
697
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 739 publications
(770 citation statements)
references
References 59 publications
48
697
1
10
Order By: Relevance
“…Consistent with previous analyses of ancient bone [8,14,15], we observe deamidation for both glutamine and asparagine (figure 4; electronic supplementary material, figure S4) that is incomplete (e.g. electronic supplementary material, figure S4) and may be, in part, derived from sample preparation.…”
Section: (A) In Vivo Post-translational Modificationssupporting
confidence: 77%
See 2 more Smart Citations
“…Consistent with previous analyses of ancient bone [8,14,15], we observe deamidation for both glutamine and asparagine (figure 4; electronic supplementary material, figure S4) that is incomplete (e.g. electronic supplementary material, figure S4) and may be, in part, derived from sample preparation.…”
Section: (A) In Vivo Post-translational Modificationssupporting
confidence: 77%
“…Now, recent advances in high-resolution mass spectrometry have resulted in a renewed interest in the utility of proteins preserved in fossils (reviewed in [9]). Ancient proteomic studies have extended the age for which biomolecules and phylogenetically informative molecular sequences can be recovered to well beyond the hypothesized limit for DNA preservation [8,[10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LC-MS/MS analysis was conducted on three (SI Appendix, Fig. S1) of the hominin bone specimens, as published previously for nonhominin bone specimens (19), as well as two additional analyses of one palaeoproteomic extract generated following a modified protein extraction protocol (52). We took measures to avoid and detect protein contamination throughout our palaeoproteomic workflow.…”
Section: Methodsmentioning
confidence: 99%
“…Orlando and his team found that the preparation lost vast quantities of fragments. But with a few tweaks to the experimental protocol, such as reducing the extraction temperature, the researchers captured ten times more scraps of DNA than before -and produced a draft of the oldest genome on record 2 .…”
mentioning
confidence: 99%